2021
DOI: 10.30564/jasr.v4i2.3135
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Off-season Rainfall of January to February 2020 and Its Socio Economic Implications in Tanzania: A Case Study of the Northern Coast of Tanzania

Abstract: This article examines the off season rainfall in northern coast Tanzania (NCT) including Zanzibar which occurred in January and February 2020 (JF). Like the JF rainfalls of 2001, 2004, 2010, 2016 and 2018, the JF (2020) rainfall was more unique in damages including loss of lives, properties and infrastructures. The study used the NCEP/NCAR reanalysis data to examine the cause of uniqueness of JF rainfall in 2001, 2004, 2010, 2016, 2018 and 2020 over NCT and Zanzibar. These datasets include monthly mean u, v wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(56 reference statements)
2
3
0
Order By: Relevance
“…Higher rainfall at Mkoani followed by Wete which indicates that Mkoani is leading compared to other regions. The impacts of the observed higher rainfall over most areas of Zanzibar is in concurrence with [24] who noted that higher rainfall in OND 2019 has resulted into a number of socioeconomic stresses including the death of people, damage to electric poles resulting in power shortage for several days (at Mwakaje and Mwera)also trees and vegetation plantation were affected. As for the climate influence on T max and T min at Unguja and Pemba, the presented results have shown that T max was increasing at the rate of 0.035 and 0.0169˚C/yr, respectively.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Higher rainfall at Mkoani followed by Wete which indicates that Mkoani is leading compared to other regions. The impacts of the observed higher rainfall over most areas of Zanzibar is in concurrence with [24] who noted that higher rainfall in OND 2019 has resulted into a number of socioeconomic stresses including the death of people, damage to electric poles resulting in power shortage for several days (at Mwakaje and Mwera)also trees and vegetation plantation were affected. As for the climate influence on T max and T min at Unguja and Pemba, the presented results have shown that T max was increasing at the rate of 0.035 and 0.0169˚C/yr, respectively.…”
Section: Discussionsupporting
confidence: 81%
“…Annual and seasonal rainfall rates of Unguja and Pemba, wind pattern (southeast and northeast monsoon), and annual and seasonal temperature rates (maximum, minimum and daily mean). Also [24] has shown that the long-term average maximum temperature during March to May (MAM) season for Zanzibar ranged from 32.4˚C for Unguja and 31.6˚C for Pemba; while the minimum ranged from 22.7˚C and 23.1˚C for Unguja and Pemba respectively.…”
Section: Study Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results for the correlation between the water melon production and weather parameters shows that the MAM rainfall at Chake Chake district was high (r = 0.5) but not significant indicating that there exists little production of watermelon during MAM season as supported by anecdotal response Figure 8. Also this results in well supported by [5] who noted that the peak MAM rainfall for Pemba is during May and that of Unguja is during April indicating that the period between March and April for Pemba can be good for production of watermelon. Also results in Table 1 for Micheweni revealed a correlation of (r = 0.2 and r = 0.03), though not significant between watermelon production during MAM and OND, respectively.…”
Section: The Influence Of Weather or Climate Parameter On Watermelon ...supporting
confidence: 80%
“…composts), paste sides and farmers selfmotivation, but also climate and weather fluctuations and changes seems to be most important production deciding factor. Since most agricultural activity in East Africa and Zanzibar in particular are climate driven [5] [9] [10] and also the agricultural activities in Zanzibar are also rain fed, therefore is highly threatened by the consequences of climate change, thus the watermelon production as an adaptive measure in Zanzibar is also subjected to seasonal variability (fluctuations). The 4th IPCC report noted that by 2020 in Africa all agricultural rain fed yields would be reduced by 50% due to the climate change stress as also noted by [11].…”
Section: Seasonal Variability Of Watermelon Production In Zanzibarmentioning
confidence: 99%